Antibacterial Effects of Ziziphus mauritiana (Lam) Leaf Extract Against Vibrio cholerae - Febriza, Ami; Faradiana, Shelli; Abdullah, M Fadly (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Introduction: In Indonesia, treatment using leaves as traditional medicine is still firmly integrated with the community to overcome various health problems experienced, one of which is treatment using Bidara leaves (Ziziphus mauritiana). Nowadays, in addition to chemical drug treatment, many researchers have also developed about herbal medicine. Bidara leaf is a potential source of antibacterial agent. Methods: The method used well diffusion. Antibacterial activity has shown in the inhibition zone. Total samples were 25 samples divided into five groups; groups treated with Purple Eggplant peel extract 25 %, 50 %, 75%, positive control (erythromycin), and negative control. Data were analyzed with the Kruskal-Wallis test. Results: Bidara leaf extract inhibited V. cholerae growth characterized by an inhibition zone that formed. Means of inhibition zone diameter were statistically significantly different between groups (p-value = 0.001. Conclusions: Bidara leaf extract with 25%, 50%, and 75% concentrations has the same ability as nystatin in inhibiting the growth of V. cholera.